Implementation Of Learning Management System (LMS) Learning Media At Muhammadiyah 2 SMA Yogyakarta - Fauziya Nailil Husna; Hanif Cahyo Adi Kistoro; Prima Rosita Sari; Syafira Intan Muhliana (Linguanusa : Social Humanities, Education and Linguistic, 2023)
Introduction to The Problem : The occurrence of the COVID-19 pandemic is increasingly rampant, the thing that is being hotly discussed is related to face-to-face learning into virtual face-to-face . That correct occurs in an early learning  conducted by stare advance Becomes virtual stare. Purpose : Based on the SE Minister of Education and Culture an appeal for doing education online and working from the house to avoid the spread of COVID-19. The moment occurs the COVID-19 pandemic; there are changes in implementation One of the media that can be held for online learning is the Learning Management System (LMS) as implemented in SMA Muhammadiyah 2 Yogyakarta. Design/methods/approach : The destination of the study is to know the implementation of the learning media Learning Management System (LMS) at SMA Muhammadiyah 2 Yogyakarta. In addition, for knowing factor support and inhibitor in online learning performance using LMS. Subject from the study this namely five teachers with different eye lessons . Data collection techniques in research this use observation , interview and documentation with instruments that have been compiled . Data validity in the study this use triangulation data source . Data analysis techniques using procedure data reduction , data presentation and data interpretation. Findings : The results of this study find two Things important that is first , the implementation  of the Learning Management System conducted through stages of planning , implementation and evaluation . Finding second is existence factor supporters like existence data plan help , strong signal , and adequate devices. The temporary factor of the barrier is no existence quota , no existence signal , and devices that do not adequate . Research implications/limitations : Studies still have limitations on subjects and data processing. Originality/value : For the next researcher, it is hoped that could dig and research further so that could add more results  deep